Resolving the Willingness-to-Pay Paradox: A Pricing Justice Perspective on Destination Loyalty in Emerging Tourism Contexts - Susanto, Eko; Modupe, Ajayi Olubunmi (Journal of Consumer Studies and Applied Marketing, 2025)
Traditional tourism pricing models often fail to explain the "Willingness-to-Pay (WTP) Paradox," where high environmental commitment among tourists does not translate into financial readiness. This study moves beyond generic satisfaction-loyalty frameworks by empirically adjudicating the structural mechanisms linking justice-based pricing antecedents to destination loyalty in volatile emerging markets. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Importance-Performance Matrix Analysis (IPMA) with a sample of 350 tourists, the research examines how price transparency, integrity, and social comparison influence behavioral intentions. The findings reveal a critical theoretical shift: price integrity significantly outperforms mere informational transparency in establishing perceived price fairness. Furthermore, the analysis validates a sequential dual-mediation framework, demonstrating that the path from pricing justice to loyalty is strictly contingent upon the formation of both perceived destination value and destination trust. IPMA results identify a structural asymmetry: these relational mediators—value and trust—have the highest predictive importance but exhibit suboptimal performance, placing them in the high-priority quadrant for intervention. This research extends Equity Theory by demonstrating that loyalty in nascent regulatory environments is anchored in institutional reliability rather than transient price advantages. Ultimately, it offers Destination Management Organizations (DMOs) a data-driven roadmap to harmonize pricing strategies and secure competitive resilience.